Engaging with Contemporary Culture: Christianity, Theology and the Concrete Church - Howes, Graham (Implicit religion, 2007)
The article reviews the book "Engaging With Contemporary Culture: Christianity, Theology and the Concrete Church," by Martyn Percy.